Model of ligand-triggered information transmission in G-protein coupled receptor complexes - Jones, Roger D.; Jones, Alan M. (Frontiers in Endocrinology, 2023)
We present a model for the effects of ligands and the surrounding environment on information transmission in G-Protein Coupled Receptor (GPCR) complexes. The model is built ab initio entirely on principles of statistical mechanics and tenets of information transmission theory and was validated in part using agonist-induced effector activity and signaling bias for the neurotensin- and adrenergic-mediated signaling pathways, with in vitro observations of phosphorylation sites on the C tail of the GPCR complex, and single-cell information-transmission experiments. The model extends traditional kinetic models that form the basis for many existing models of GPCR signaling. It is based on maximizing the rates of entropy production and information transmission through the GPCR complex. Relevant for drug designers, the model predicts that (1) phosphatase-catalyzed reactions on the C-tail of the GPCR are responsible for controlling the signaling activity, (2) the association, as opposed to the dissociation, of GTP-bound G protein with the GPCR complex is another control reaction, (3) control of signaling activity requires targeting both inhibition and stimulation steps simultaneously, and (4) biased signaling can be agonist concentration dependent.